2020
DOI: 10.21203/rs.2.23789/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Antimicrobial resistance among GLASS pathogens in conflict and non-conflict affected settings in the Middle East: A systematic review

Abstract: Background: In spite of the evident general negative effects of armed conflict on countries’ health systems and populations’ health outcomes, little is known about similar impacts of conflicts on the spread of antimicrobial resistances (AMR). This review was to address this evidence gap and describe:1. Patterns of AMR in the Middle East (ME) and resistance profiles of pathogens included in the Global AMR Surveillance System (GLASS) supported by the World Health Organization;2. Differences in proporti… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 34 publications
3
10
0
Order By: Relevance
“…They have been described in most of selected papers. Other systematic reviews, conducted on AMR in the Middle East [77] and Africa [78], have reported the same results.…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…They have been described in most of selected papers. Other systematic reviews, conducted on AMR in the Middle East [77] and Africa [78], have reported the same results.…”
Section: Discussionsupporting
confidence: 67%
“…Such infections might require hospitalization and intravenous injection of carbapenem antibiotics. In this review, the carbapenem-resistance proportion among GLASS Enterobacteriaceae appears like other reports from Africa [78] and the Middle East [77], but higher than those described in most European countries [84]. In this context, the prevalence of carbapenemase-producing K. pneumoniae and E. coli, per 10 000 hospital admissions, presents an average of 1.3 (6.0 in Italy, 0.02 in Norway).…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…Alternatively, a less preferable approach, is the utilization of microbiology data alone (laboratory-based surveillance) without clinical and epidemiological data. Most national and supranational AMR networks rely solely on laboratory data to trace changes of antimicrobial susceptibility in space and time [7,[19][20][21][22]. A recent review on supranational networks performing AMR surveillance in LMICs showed the heterogeneity of data due to lack of standards on the composition and activities of surveillance networks [7], and the majority (80%; 39/49) describe AMR based on samples sent to laboratory for clinical purposes (Table 2).…”
Section: Strategies Of Identifying Amr / Drug-resistant Infections (Dri)mentioning
confidence: 99%
“…Just recently, the first review specifically addressing the antimicrobial resistance evidence gaps in the Middle East was published. Not surprisingly, the authors found no data available for children from conflict-affect settings [57]. Common infections worldwide are becoming more difficult to treat; however, children injured during armed conflict are also inevitably at risk for acquiring MDRO.…”
Section: Antimicrobial Resistance In Conflictmentioning
confidence: 99%